PERSEPSI GENDER SOFT MASCULINITY KALANGAN PENGGEMAR BTS DI RIAU - Afli, Dhuhafa; Olivia, Yessi (Fakultas Ilmu Sosial dan Ilmu Politik Universitas Riau, 2023)
The transnational saturation of South Korean popular culture is experiencing a rapid expansion in the global market which is referred to as the Korean Wave. A major component of the Korean Wave is South Korean pop music (KPOP) which have gained significant popularity due to their highly attractively crafted image that represents the South Korean aesthetic. It explores South Korean popular culture as the impact of globalization on the performance of new gender practices on the value of masculinity which is referred to as soft masculinity. BTS, one of the KPOP idols, has experienced a shift in showing their masculinity, from showing masculinity that is involved towards hegemonic norms to challenging socially accepted values as men by carrying out gentle masculinity. This study uses the theory of perception as a theoretical basis in gaining perceptions among female fans and being aware of objects and events that have occurred stored in popular culture phenomena and interpreting the meaning of soft masculinity. Using descriptive qualitative research methods to explain popular culture phenomena, and data collection techniques from interviews with BTS female fans as informants. The results of the study concluded that fans' perceptions of the masculinity concept of BTS are subjective and constructed primarily on cultural differences. Keywords: South Korea, Popular Culture, Gender, Soft Masculinity, Korean Wave, KPOP, Bangtan Boys (BTS)